Antioxidant activity, antimicrobial and effects in the immune system of plants and fruits extracts. Issue 2 (2nd April 2016) - Reyes-Munguía, Abigail; Carrillo-Inungaray, María Luisa; Carranza-Álvarez, Candy; Pimentel-González, Diana J.; Alvarado-Sánchez, Brenda
ABSTRACT: Nowadays, medicinal plants, and fruits and vegetables with antioxidant and antimicrobial activity are increasingly studied. In this review, the impact of the medicinal plant extracts on the immune system was discussed. The first part described the phenomenon of oxidative stress, followed by the mechanisms involved in the antioxidant activity and finally discussed on the evaluation of the antioxidant activity of plants and fruits. The second part revised the works that discuss about the antimicrobial activity of plants and fruits extracts, emphasizing in the factors that influence the evaluation of such characteristic. Finally, in the third part,  studies on the effect of the plant extracts over the immune response were discussed, describing the results of the enhancer effects, as well as those of the suppressing ones. This work allowed us to discern the necessity of a wider research on the chemical composition of the natural extracts, in order to establish a correlation with the effects observed in health.